2022
DOI: 10.1371/journal.pone.0273047
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable diseases prevention in remote areas of Vietnam: Limited roles of health education and community workers

Abstract: Objective This study aimed to measure the exposure of residents to health education messages about non-communicable diseases (NCD)-related risk factors, and activities of village health workers (VHWs) in NCDs prevention and control in the mountainous setting of Vietnam. Method A cross-sectional study was performed in Dap Thanh commune (Ba Che, Quang Ninh province, Vietnam), a mountainous area. There were 151 residents aged 18 years or above recruited for this study. Information regarding exposure to messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Based on stakeholder feedback, future education topics to be considered for further expansion of VMWs roles could focus on non-communicable diseases, as these are prevalent in most populations and could be useful in preventing long lasting complications. Multiple projects elsewhere have successfully equipped volunteers with the necessary tools and education to conduct monitoring of non-communicable diseases [11,[39][40][41]. Promising tasks might include measuring blood pressure, measuring blood glucose levels and assisting community members with taking or administering medication.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Based on stakeholder feedback, future education topics to be considered for further expansion of VMWs roles could focus on non-communicable diseases, as these are prevalent in most populations and could be useful in preventing long lasting complications. Multiple projects elsewhere have successfully equipped volunteers with the necessary tools and education to conduct monitoring of non-communicable diseases [11,[39][40][41]. Promising tasks might include measuring blood pressure, measuring blood glucose levels and assisting community members with taking or administering medication.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 58 Likewise, interpersonal communication is widely employed to facilitate the efficient dissemination of about pandemics within the population and enhances two-way communication at the household and community levels. 56 , 57 Furthermore, education and training at the interpersonal level are essential for improving the intrinsic abilities of a person to avoid health-risk behaviors. 59 On the other way, a pilot study on peer health education for NCD prevention in Bangladesh, Ethiopia, and Palau showed that peer health education is an effective strategy for preventing NCDs in resource-limited settings; 60 however, in this study, the method was not common in dealing with NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature confirms that effective communication about NCDs and bringing sustained behavioral change requires the active involvement of various stakeholders such as government, health sector, non-governmental organizations, religious leaders, community leaders, media, teachers, students, and different associations, healthcare workers and so on in bridging the gap between knowledge and practice. 56,57 This indicates that the prevention and control of NCDs require more attention and cross-sectoral participation of various stakeholders. 58 On the other hand, the study found that various communication methods were employed to inform and raise awareness about NCDs and the associated risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on stakeholder feedback, future education topics to be considered for further expansion of VMWs roles could focus on non-communicable diseases, as these are prevalent in most populations and could be useful in preventing long lasting complications. Multiple projects elsewhere have successfully equipped volunteers with the necessary tools and education to conduct monitoring of noncommunicable diseases [11,[39][40][41]. Promising tasks might include measuring blood pressure, measuring blood glucose levels and assisting community members with taking or administering medication.…”
Section: Strengths and Limitationsmentioning
confidence: 99%